Masculine gender norms, male circumcision, and men's engagement with health care in the Dominican Republic. Issue 5 (3rd May 2020) - Wiginton, John Mark; Fleming, Paul J.; Barrington, Clare; Donastorg, Yeycy; Lerebours, Leonel; Brito, Maximo O.
ABSTRACT: Overall, adult men are less likely to seek and receive health care than women, but male circumcision for HIV prevention has been successful in engaging men in health services. The purpose of this paper is to examine the relationship between masculine norms and health care-seeking among men participating in a voluntary male medical circumcision (VMMC) programme in the Dominican Republic (DR). We employed a mixed methods approach integrating survey data collected 6–12 months post-circumcision ( n = 293) and in-depth interviews with a sub-sample of these men ( n = 30). In our qualitative analysis, we found that health care-seeking is connected to masculine norms among men in the DR, including the perceptions of medical facilities as feminine spaces. Participants' narratives demonstrate that male circumcision programmes may facilitate men overcoming masculinity-related barriers to health care engagement. In quantitative analysis, we found that being concerned about being perceived as masculine was associated with health care-seeking behaviour in the past five years, though this association was not retained in multivariable analyses. Findings indicate that male circumcision programmes can familiarise men with the healthcare system and masculinise health care-seeking and utilisation, easing associated discomfort.